Ethnic intermarriage in times of social change: the case of Latvia. - Monden, C; Smits, J (2005)
We gain insight into the dynamics of ethnic intermarriage in times of social change by studying marriages between Latvians and Russians (including Belarussians and Ukrainians) that occurred in Latvia before and after independence from the Soviet Union. Before independence, ethnic intermarriage was already rather common, involving about 17% of the marriages annually. Since independence, intermarriage between Russians and Latvians has increased substantially. Part of this increase can be explained by selective emigration, but at least half of it may be due to integrative processes. Although there were more marriages between Russian men and Latvian women before independence, the gender pattern reversed after independence. Intermarriage levels were the highest among the less educated, children of mixed couples, partners with similar educational levels, and people in the countryside.